Reading in between nook and cranny - Abdul Razak, Muhammad Aiman Haqiem; Ayob, Muhammad Nasamuddeen Hakimie; Roslan, Ahmad Darwish Adam; Hisham, Ahmad Aqil (Universiti Teknologi MARA, Kedah, 2018)
People nowadays really appreciate privacy. Specifically, for those with social anxiety and would rather go and live in a cave rather than sitting in a social event. For the social butterflies, they still could use some privacy we all do. We build a room consist of a computer with stable internet connection, a table, a see-through glass to see what happened inside and a sound proof wall to make sure no noises come out or come in. furthermore, people who wanted to do some research can appreciate these facilities. This includes people who wanted to study but cannot comprehend noises around them.